The Federal Council in Iraq: Between activation (constitutionally) and paralysis (politically) (Al-Mostansiriyah journal for Arab and international studies, 2025)
According to the 2005 Constitution, Iraq is a federal state with a parliamentary character, the latter consisting of two chambers, one representing the people (the Council of Representatives) and the other representing the provinces and regions (the Federation Council), but the latter has not been formed until the present time, due to constitutional issues represented by the enactment of a law by the Council of Representatives indicating (the structure of the Federation Council), which is a dangerous constitutional precedent that is not known to developed countries. The Iraqi Constitution mandates the formation of the Federation Council only after the end of the first electoral cycle, and political consensus among the ruling elite is also a contributing factor in delaying the enactment of the Federation Council law.Keywords: Federal Council, Constitution, Political paralysis, Iraq.